Analysis of the Seismic Demand of High-Performance Buckling-Restrained Braces under a Strong Earthquake and Its Aftershocks - Luqi Xie; Jing Wu; Qing Huang; Chao Tong (Advances in Civil Engineering)
The analysis of the ductility and cumulative plastic deformation (CPD) demand of a high-performance buckling-restrained brace (HPBRB) under a strong earthquake and its aftershocks is conducted in this paper. A combination of three continuous excitations with the same ground motion is used to simulate the affection of a strong earthquake and its aftershocks. A six-story HPBRB frame (HPBRBF) is taken as an example to conduct the incremental dynamic analysis (IDA). The seismic responses of the HPBRBF under one, two, and three constant continuous ground motions are compared. The IDA result indicates that the ductility and CPD demand of the BRBs under the three constant continuous ground motions are significantly larger than that excited by only one. Probabilistic seismic demand analysis (PSDA) is performed using seven near-fault ground motions and seven far-fault ground motions to consider the indeterminacy of ground motion. The probabilistic seismic demand curves (PSDCs) for the ductility and CPD demand for the HPBRB under the strong earthquake and its aftershocks are obtained in combining the probabilistic seismic hazard analysis. The results indicate that the AISC threshold value of the CPD with 200 is excessively low for a HPBRBF which suffers the continuous strong aftershocks with near-fault excitations, and a stricter threshold value should be suggested to ensure the ductility and plastic deformation capacity demand of the HPBRB.